Towards Inclusive Policy: Formal Recognition of Customary Law in the Determination of Village Boundaries Under the National Legal Framework in Indonesia - Randy Vallentino Neonbeni; Lego Karjoko; Pujiono Suwadi (Prosiding Seminar Nasional Ilmu Hukum, 2025)
Inclusive policies are a must in governance, especially at the village level that deals directly with indigenous communities. Formal recognition of customary law in the determination of village boundaries under the national legal framework is crucial to create agrarian justice and legal certainty; Its relevance focuses on the importance of local wisdom accommodation and the structure of indigenous peoples as legal subjects entitled to their territories; The final goal of this study is to formulate a model of harmonization of positive law and customary law for the determination of participatory and equitable village boundaries; The main legal basis includes the 1945 Constitution Article 18B Paragraph (2) and Law (UU) Number 6 of 2014 concerning Villages; and Regulation of the Minister of Home Affairs Number 45 of 2016 concerning Guidelines for the Determination and Affirmation of Village Boundaries. This research uses a normative juridical method with a legislative and conceptual approach; The conflict resolution offered is through a consensus deliberation mechanism facilitated by the local government while still upholding the rights of indigenous peoples.